Template guided transperineal saturation biopsy of the prostate: lessons for focal and urethra-sparing high-dose-rate brachytherapy for localized prostate cancer - Novikov, Sergey Nikolaevich; Kanaev, Sergey Vasilevich; Novikov, Roman Vladimirovich; IIlin, Nikolay Dmitrievich; Artemieva, Anna Sergeevna; Ivantcov, Alexnder Olegovich; Piskunov, Evgeniy Alexandrovich; Gotovchikova, Mariya Yurievna (Journal of Contemporary Brachytherapy, 2016)
Purpose : The aim of this work is to evaluate results of prostate transperineal saturation biopsy as a guide for focal high-dose-rate brachytherapy in patients with prostate cancer (PCa). Material and methods: Template guided saturation biopsy was performed in 67 primary patients with suspicion for prostate cancer. Biopsy was performed under ultrasonography (US) control with the help of brachytherapy grid and 5 mm distance between samples. We put special attention for accurate sampling of prostate in periurethral region. The number of cores varied from 17 to 81 (average 36 cores). Finally, in 40 patients with confirmed prostate cancer results of biopsy were used for brachytherapy planning. Results : Saturation biopsy revealed prostate cancer in 40 of 67 evaluated patients. The extent of biopsy core involvement varied from 5% to 100% (average: 57%). Focal nature of PCa (single unilateral tumor nodule) was diagnosed in 10 (25%), multifocal – in another 30 (75%) patients. Hemigland invasion was mentioned in 12 (30%) cases. Saturation biopsy detected PCa in periurethral cores in 27 (67.5%) of 40 evaluated patients. In 10 patients, the extent of involvement in periurethral cores varied between 10% and 50%; in another, 17 observations exceeded 50%. According to results obtained on saturation biopsy, we performed HDR brachytherapy with “urethra low dose tunnel” (D10ur ≤ 80-90%) in 13 patients with noninvolved periurethral cores. Theoretically, hemigland brachytherapy was possible in 12 of 40 evaluated patients with PCa. Conclusions : In low risk patients with PCa results of template guided saturation biopsy indicates high frequency (75%) of multifocal disease and high probability (67.5%) of periurethral invasion. Suitable candidates for focal HDR brachytherapy or irradiation with additional sparing of urethra can be effectively determined with the help of saturation biopsy.